การบูรณาการพุทธวิธีกับการบริหารงานท้องถิ่นของเทศบาลตำบลตาดทอง อำเภอเมือง จังหวัดยโสธร - กันยาวรรณ, พิชิต; กวีกรณ์, พ.ต.อ.มังกร (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 3 (2025): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 2 ฉบับที่ 3 : กันยายน - ธันวาคม 2568, 2025)
This research aims to: (1) examine the Buddhist principles related to public participation in Mueang district, Yasothon province; (2) analyze the patterns and levels of citizen participation in local administrative organizations within Mueang district, Yasothon province; and (3) propose Buddhist-oriented approaches for promoting public participation in the administration of Tad Thong subdistrict municipality, Mueang district, Yasothon province. The sample consisted of 224 participants. Data were analyzed using percentage, mean, and standard deviation. The findings revealed that: (1) Săranĩyadhamma (the virtues conducive to communal harmony) is not merely a religious doctrine but serves as a “humanitarian administrative principle” that effectively bridges Buddhist ethics with local public administration. Promoting governance grounded in Săranĩyadhamma represents a path toward a moral democracy and a peaceful, harmonious society. (2) Buddhist-oriented public participation in the administration of Tad Thong Subdistrict Municipality is shaped by four essential components: (1) processes of local political participation; (2) processes of Buddhist political participation; (3) the promotion of participation through Săranĩyadhamma; and (4) environmental and political learning factors. Buddhist-oriented participation extends beyond tangible political actions it encompasses mental and moral dimensions that foster peace and sustainability in local governance. The integration of political science and public administration perspectives with Buddhist principles provides a new paradigm for developing a moral democracy and compassionate administration that can serve as a model for other localities. (3) The study further proposes practical measures to enhance citizens’ quality participation in local governance based on Buddhist teachings—particularly mettă (loving-kindness), karună (compassion), and Săranĩyadhamma (principles of harmony) which emphasize unity, mutual understanding, and solidarity between citizens and administrators in participatory governance.